Organizational capacities of cocoa associations from the southeast of the department of Boyacá, Colombia - Vargas Martínez, Andrés Felipe (2022)
In a globalized and competitive context, the performance of organizations can be measured with tools that integrate different indicators to measure different variables. The objective of this project was to determine the Organizational Capacity Index (OCI) of ASOCACAM, ASOPROCALEN, and ASACASAM, cocoa associations of the Southeast of the Department of Boyacá, Colombia. For this purpose, a case study was conducted, corresponding to a descriptive research study with an exploratory scope, under an interpretive, not probabilistic, qualitative and inductive paradigm, using the Organizational Capability Index that has eleven variables grouped in four major areas: 1) Organization, 2) Strategy, 3) External scope, and 4) Internal scope. Once the individual weightings had been obtained, the evaluations were conducted based on an ideal performance percentage (100% overall, 31.37% in Organization, 9.96% for the Strategy item, 17.71% in the External area, and 40.96% in the Internal sphere). As a result, the associations evaluated under this methodology did not even reach close to half the ideal weighted performance, proving the level of Organizational Capacity of the cocoa associations studied to be deficient.